Trend trading : - Brown, Kedrick F. (J. Wiley & Sons, 2006)
Written in a straightforward and accessible style, Trend Trading teaches you how to trade equity trends with sound money management discipline, from the individual stock level to the whole portfolio level. Tailored to investors who want to use elements of trend following strategies in their equity portfolios, Trend Trading presents unique investment tools and advanced technical analysis methods in simple, commonsense terms.